Efficient Procedure Improving Precision of High Conditioned Matrices in Electronic Circuits Analysis - Cerny, David; Dobes, Josef; Banas, Stanislav (Společnost pro radioelektronické inženýrství, 2018)
In this article, we propose several improvements that could be done to SPICE simulator. The first is based on a functional implementation of device models. The advantages of functional implementation are demonstrated on basic Shichman-Hodges model of MOS transistor. It starts with a description of primary algorithms used in SPICE simulator for the solution of circuits with nonlinear devices and identify the problems that can occur during simulations.Main part of the article is devoted to improved factorization procedure for simulation of the nonlinear electronic circuits. The primary intention of the proposed method is to increase final precision of the result in a case of high condition linear systems. The procedure is based on a use of the iterative methods for solution of nonlinear and linear equations. Utilizing those methods for one iterative process helps to reduce memory consumption during simulation computation, and it can significantly improve simulation precision. The procedure allows to use enumeration with definable precision in a very efficient way.
Keywords: SPICE simulator; functional programming; Lisp; iterative methods; factorization procedures; conditionality of linear systems; simulation precision